Pelatihan Perangkat Rukyah di Pondok Pesantren Fadhlul Wahid Ngangkruk Grobogan Sebagai Penunjang Efektivitas Pelaksanaan Pengamatan Hilal - Mujab, Sayful; Huda, Muhammad Nurul (Institut Agama Islam Negeri (IAIN) Kudus, 2025)
Rukyah Equipment Training at the Fadhlul Wahid Ngangkruk Grobogan Islamic Boarding School to Support the Effectiveness of Hilal Observation Implementation. This Community Service activity aims to improve the capacity of students and ustadz of the Fadhlul Wahid Ngangkruk Grobogan Islamic Boarding School in mastering rukyah devices to support the effectiveness of hilal observations. The method used was Participatory Action Research (PAR) with a practice-based training approach, so that participants not only received theory but also actively participated in problem identification, solution formulation, and field practice. The results of the activity showed significant achievements, where the level of understanding of participants reached 90% in the use of cameras and rukyah devices, and 85% in mastery of theoretical material, although there were still limitations in certain instruments. The implication of this activity is the need for continuous training and intensive mentoring to optimize instrument mastery. The suggestion is that this practice-based training model can be adopted by other Islamic boarding schools as a strategy to strengthen the role of Islamic boarding schools in the development of astronomy and determining the beginning of the Hijri month.